Optimizing maturity index calculation of groundnut in selected varieties at Coimbatore condition: Optimizing maturity index calculation of groundnut in selected varieties at Coimbatore condition - R SANGEETHA VISHNUPRABHA; P L VISWANATHAN; S MANONMANI; L RAJENDRAN; T SELVAKUMAR (Journal of Oilseeds Research, 2020)
The present study was taken up to evaluate the efficiency of the maturity index calculating methods viz., shell out method, seed hull ratio maturity index, hull scrape method and maturity profile board (MPB) method in determining the maturity duration of ten groundnut varieties CO 7, ICGV 07222, VRI 6, VRI 8, GPBD 4, VRI 3, Chico, Gangapuri, ICGV 91114 and ICGV 93468 at Coimbatore. In Shell out and hull scrape method maturity indices ranged from 70- 80% and in seed hull ratio maturity index it ranged from 2.9-3.6 which revealed the highest number of matured pods with maximum weight. In hull scrape method and MPB the colour of mesocarp exactly revealed maturity status of groundnut pods with a strong correlation with yield. Thus, maturity index in groundnut is more reliable when calculated by hull scrape method in combination with maturity profile board (MPB) to determine the days until digging.